Selecting high quality and effective choral literature for a choral ensemble - Yoho, Joshua G. (Kansas State University, 2012)
This report is for the beginning choral music educator or music education student who seeks guidance when selecting repertoire for their advanced elementary or beginning middle school choir. I attended the 2011 Kansas Choral Directors Association conference. Conferences such as these are great resources for the novice choral educator and even the veteran teacher. Choral reading sessions are excellent ways to find new and quality repertoire, because the directors that select the music spend a good amount of time researching and selecting songs. In determining what factors directors use to choose repertoire for their choirs, a survey was developed and administered to forty Kansas music educators at one of the reading sessions which asked the following three questions: 1) What is the likelihood that you would use this song in a concert or program? The next two are questions in which I asked (these two were based on a ‘disagree or agree’ scale): ‘This song has good educational value for the students’ and ‘I can teach many elements of music within this song.’ Evidence is shown from other master educators of various levels that choosing appropriate, worthy, and challenging repertoire is crucial to the success of the choral program.
Keywords: Choosing choral repertoire; High quality; Effective; Appropriate; Music Education (0522)